2022
DOI: 10.3389/fnins.2022.820155
|View full text |Cite
|
Sign up to set email alerts
|

Visual Evoked Potentials to Monitor Myelin Cuprizone-Induced Functional Changes

Abstract: The visual system is one of the most accessible routes to study the central nervous system under pathological conditions, such as in multiple sclerosis (MS). Non-invasive visual evoked potential (VEP) and optical coherence tomography (OCT) were used to assess visual function and neuroretinal thickness in C57BL/6 taking 0.2% cuprizone for 7 weeks and at 5, 8, 12, and 15 days after returning to a normal diet. VEPs were significantly delayed starting from 4 weeks on cuprizone, with progressive recovery off cupriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…4B and C). As VEP latency time is correlated with optic nerve de-and remyelination, we implemented epidermal flash VEP measurements (3 trains of 20 stimuli, 10 µs duration, 1 Hz frequency) of both eyes during both de-and remyelination (Marenna et al, 2022). Significantly increased latency times were observed at the end of cuprizone administration indicating demyelination of the optic nerve, and they were significantly decreased upon PDE4D inhibition during remyelination, indicating functional remyelination (repeated measure two-way ANOVA with Sidak's multiple comparison test; F (2,18)= 63.27; **P ≤ 0.01; ***P ≤ 0.005) (Fig.…”
Section: Pde4d Inhibition Enhances Remyelination and Thereby Promotes...mentioning
confidence: 99%
“…4B and C). As VEP latency time is correlated with optic nerve de-and remyelination, we implemented epidermal flash VEP measurements (3 trains of 20 stimuli, 10 µs duration, 1 Hz frequency) of both eyes during both de-and remyelination (Marenna et al, 2022). Significantly increased latency times were observed at the end of cuprizone administration indicating demyelination of the optic nerve, and they were significantly decreased upon PDE4D inhibition during remyelination, indicating functional remyelination (repeated measure two-way ANOVA with Sidak's multiple comparison test; F (2,18)= 63.27; **P ≤ 0.01; ***P ≤ 0.005) (Fig.…”
Section: Pde4d Inhibition Enhances Remyelination and Thereby Promotes...mentioning
confidence: 99%
“…We show that whereas uninjured oligodendrocytes in the optic nerve are mostly resilient to cuprizone (consistent with previously published literature; Yang et al, 2009 ; Kojima and Hayashi, 2018 ), post-injury born oligodendrocyte lineage cells in the injury site are susceptible to cuprizone, which thus reduces repopulation of the injury site by new oligodendrocytes and improves axon regeneration. Although cuprizone does not kill the surviving MOs located beyond the injury site in the optic nerve, it injures and affects them, as cuprizone elicits toxicity within the visual system ( Marenna et al, 2022 ; Namekata et al, 2014 ); we found a 10% decrease in the MBP signal after the cuprizone diet in the region of the optic nerve distal to the ONC site. Thus, although the surviving ONC injury MOs (located beyond the injury site) have reduced capacity for growing sheaths and myelinating, some of them spontaneously re-acquire myelinating capacity ( Duncan et al, 2018b ).…”
Section: Discussionmentioning
confidence: 66%
“…It has been shown that following cuprizone-induced demyelination, loss of excitatory synapses in the dLGN is accompanied by a shift toward inhibitory signaling ( Araújo et al, 2017 ). VEP activity in the cuprizone model corresponds to demyelination and remyelination, indicating that VEP reflects demyelinating activity as it does in MS patients ( Marenna et al, 2022 ). This also suggests that VEPs may reflect the efficacy of remyelinating therapy in preclinical models, providing utility in determining neuroprotective strategies in MS. A study by Crawford et al (2009) showed that there is a limited window of time following demyelination in the cuprizone model in which neuronal function can be recovered.…”
Section: Investigating Neurodegeneration In Ms and Disease Modelsmentioning
confidence: 99%